A Toolkit for Remote Laboratory Design & Development - Lindsay, Euan; Murray, S.; Stumpers, B. (Stipes Publishing LLC, 2011)
Remote laboratories are an increasingly prevalent instructional tool for undergraduate engineering laboratory classes. This increased prevalence brings with it a need to change the model of how remote laboratories are developed. The earlier remote laboratories were developed by individual academics combining their discipline-specific skills with their own ability to implement remote operation. This “cottage industry” model allows for significant local innovation; however it does not support widespread or sustainable implementation of remote laboratories. In order to make remote laboratories a mainstream technology, it is essential that potential academic users are well informed and well supported in considering remote laboratories. There are some well-developed and well-established systems for controlling equipment remotely; what has been missing has been the organizational scaffolding to facilitate the engagement of academics. This paper reports on a resource kit developed by the Australian Labshare project that provides this assistance. This resource kit is intended to provide academics with the resources, information and tools that they need to get started with remote laboratories – building them, using them, and understanding their educational outcomes.